2011
DOI: 10.1590/s0104-11692011000600016
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate students in orthopedic nursing care

Abstract: This study identifies some undergraduate nursing students' imaginary manifestations concerning themselves and care delivered to patients with orthopedic and/or trauma disorders. The Social Poetics method was used and the research group was composed of 15 undergraduate students. Only the categories and subcategories exclusively related to the "student" are presented in this paper. Data revealed that care provided by orthopedic nursing students is the result of a care relationship that emerges from their sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…In another study, it was found that care provided by orthopedic nursing students is the result of a care relationship that emerges from their sensitivity toward patients and their own knowledge, skills and attitudes (21). Also, it has been reported that the quality nursing and safety of patient care are significantly influenced by the number of nurses in charge in each unit, their workload and the nurse-patient proportions (15). Hallin and Danielson introduce low nurse-patient relationship as an indicator for low quality nursing care (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, it was found that care provided by orthopedic nursing students is the result of a care relationship that emerges from their sensitivity toward patients and their own knowledge, skills and attitudes (21). Also, it has been reported that the quality nursing and safety of patient care are significantly influenced by the number of nurses in charge in each unit, their workload and the nurse-patient proportions (15). Hallin and Danielson introduce low nurse-patient relationship as an indicator for low quality nursing care (22).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the prevalence of femur and hip fractures, several studies have focused on these fractures (3,4), and its hospital costs (6). One study also focused on the experiences of undergraduate nursing students in orthopedic units (15). Another study investigated the functional outcomes after hip fractures (2).…”
Section: Introductionmentioning
confidence: 99%
“…The main and secondary temporary indicators will be used during the bathing observation of patients in postoperative of Total Hip Replacement, and their development will be monitored. Cameron et al 33 identified some undergraduate nursing students' imaginary manifestations concerning themselves and care delivered to patients with orthopedic and/or trauma disorders. The Sociopoetic method was used and 15 undergraduate students were tested.…”
Section: General Reviewmentioning
confidence: 99%